27.5k views
2 votes
2(x + 3) = x - 4, what is the answer?

User C Graphics
by
4.8k points

2 Answers

2 votes

Answer:

x=-10

Explanation:

2(x + 3) = x - 4

Distribute the 2

2x+6 = x-4

Subtract x from each side

2x-x+6 = x-x-4

x+6 = -4

Subtract 6 from each side

x+6-6 = -4-6

x=-10

User Elad Weiss
by
4.2k points
3 votes

Answer:

-10

Explanation:

Isolate the variable, x. Note the equal sign, what you do to one side, you do to the other. Remember to follow PEMDAS.

First, distribute 2 to all terms within the parenthesis:

2(x + 3) = 2(x) + 2(3) = 2x + 6

2x + 6 = x - 4

Isolate the variable, x. Subtract 6 and x from both sides

2x (-x) + 6 (-6) = x (-x) - 4 (-6)

2x - x = -4 - 6

x = -10

-10 is your answer for x.

~

User Matthew Usurp
by
5.7k points